Competency mapping to develop human resources for Indonesia's sugarcane agroindustry in the Industry 4.0 era - M. Mursiti; Illah Sailah; M. Marimin; Muhammad Romli; Alex Denni (Cogent Business & Management, 2024)
Modernisation of the sugar industry in Indonesia, particularly at the off-farm level, has been slow, with most sugar factories still using old factory machinery. However, this can be improved through the use of technology to build a sustainable sugar industry. Technological advances in the Industry 4.0 era require the preparation of professional human resources, ready to compete in the global arena. In relation to these conditions, this study aims to evaluate technology in the sugarcane production process and to map the competency units of human resources in the sugarcane production process. The research method to evaluate the technology in the sugarcane production process uses two decision-making methods, namely non-numerical and numerical decision-making. The recommendation obtained is that the cut-load-transport section is a priority technology to be replaced by a new technology. The results of the evaluation were then used to map the competence units of human resources in sugar production. Competency unit mapping was carried out in the cut-load-transport and milling sections and then combined by adopting the existing refined crystal sugar work competency standards. The results of the competency mapping design can be used by sugar factories to increase the productivity of human resources in sugar factories, which does not yet exist in Indonesia.
Keywords: 650; Cane sugar agro-industry; competency mapping; human resources; Industry 4.0